Advertisement vs Societal Based Marketing Communication : An Empirical Analytic Comparison vis-a-vis Profit Contribution - Banerjee, Sujata; Mandal, Kaushik (Indian Journal of Marketing, 2018)
This research was carried out in a crucial time of transition when ad-believability is showing downward tendency and marketers earnestly require alternative tools for better customer connect. Appropriate reviews of literature helped us to understand how social spending can be used as an alternative to generate a positive impact on profitability alongside advertisement spending. Furthermore, to study empirically this conceptual proposition, we developed time series based ordinary least square linear regression model. Regression analysis was also done for the logarithmically transformed variables to know the relationship between the log of dependent and log of independent variables. Then, for each company, both the linear and log-linear models were compared to know the best fit model and by which the efficacy of societal spending considering profit impact of advertisement expenditures as reference was verified. For the purpose of building the said model, we employed 15 years' annual profit societal and advertisement expenditure data for 19 companies. The results indicated the efficiency of spending on core societal issues towards profit contribution in comparison to advertisement expenditure. The results further helped us to conclude the complementary role of societal spending along with advertisement spending on strategic brand building.